2017
DOI: 10.1016/j.jor.2017.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Soft-tissue damage during total knee arthroplasty

Abstract: Although underlying pathomechanisms are well known and presented, clinical orthopedic research has so far not addressed this issue. In context of physical training, positive effects regarding postoperative recovery might be possible if more attention is paid to prepare involved muscle preoperatively to TKA (prehabilitation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 80 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…The use of a tourniquet during TKA can clear the visual field clear and facilitate surgery, but can often cause postoperative pain and discomfort in the thigh muscles of the targeted limb [ 23 ]. It had been indicated that the non-use of tourniquets during TKA can reduce muscle and soft tissue injury in the targeted limb, relieve postoperative thigh muscle pain, shorten the length of hospital stay, and thus promote the early functional recovery of the operated knee [ 24 ]. In this study, the lower limbs were lifted for 30 s to expel blood during the operation and the blood was not extruded using a blood drive belt.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a tourniquet during TKA can clear the visual field clear and facilitate surgery, but can often cause postoperative pain and discomfort in the thigh muscles of the targeted limb [ 23 ]. It had been indicated that the non-use of tourniquets during TKA can reduce muscle and soft tissue injury in the targeted limb, relieve postoperative thigh muscle pain, shorten the length of hospital stay, and thus promote the early functional recovery of the operated knee [ 24 ]. In this study, the lower limbs were lifted for 30 s to expel blood during the operation and the blood was not extruded using a blood drive belt.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, tourniquets loosening or slipping resulting in an increased hemorrhage was tracked by SACM and within 30 s had identified a re-bleed from the arm site and began re-tightening the tourniquet. Initial design focused on re-tightening if the tourniquet loosened, but SACM could additionally be adapted to periodically loosen, providing re-infusion to the extremity to help manage limb survival [19][20][21]. Next, we highlighted the effect a secondary internal hemorrhage had on SACM.…”
Section: Discussionmentioning
confidence: 99%
“…An intentional periodic loosening can also be integrated into the algorithm allowing for reperfusion of viable tissue distal to the TKT site. This can be beneficial for instances where prolonged TKT use is required to prevent tissue necrosis, extensive nerve damage, and potential limb preservation once surgical intervention is possible [18][19][20].…”
Section: Discussionmentioning
confidence: 99%